Športna vzgoja v primarnem izobraževanju v državah Evropske unije - Črtomir Matejek (Journal of Elementary Education, 2020)
Physical Education in Primary Education in EU Countries. The main aim of this paper is to compare the representation of physical education in primary education in the countries of European Union and to explain the effects of sports activities in child’s development. For at least twenty years experts have pointed to the lack of spontaneous movement in childhood. Therefore, sports activity is suitable for maintaining good health and proper physical fitness. Physical education represents a large proportion of children’s sports activities and has positive effects on a child’s holistic development. EU countries allocate physical education of children in primary school different amounts of attention. To physical education about half of European countries devote 10% of the total time of school curriculum, Hungary, Croatia and Slovenia to 15%, while Ireland only 4%. These findings suggest that among EU countries, there are very large differences in the number of hours devoted to physical education and that designers of primary education in Europe perceive physical education as less important than other subjects.